Toxicity and mechanism of mesoporous silica nanoparticles in eyes. Issue 25 (22nd June 2020) - Chen, Xia; Zhu, Shuang; Hu, Xisu; Sun, Dayu; Yang, Junling; Yang, Cao; Wu, Wei; Li, Yijian; Gu, Xianliang; Li, Minghui; Liu, Bo; Ge, Lingling; et al.
Abstract : It aims to explore the toxicity and mechanism of large-surface-area MSiNPs and MSiNPs-Ag + exposed to hCEC cells and cornea. A protein corona-based therapy was proposed to treat MSiNPs and MSiNPs-Ag + induced corneal damage and dry eye. Abstract : The study on the safety of nanomaterials in eyes is still in its early stages. In this study, we put our focus on the effect of one important nanoparticle feature – large surface area – to assess eye safety. To this end, mesoporous silica nanoparticles (MSiNPs) were for the first time employed as a model to evaluate their toxicity in eyes. The porosity of the MSiNPs endows them with a large surface area and the ability to attach to surrounding chemical or biological molecules, further enhancing their surface reactivity and toxic effects. Therefore, to better mimic MSiNP exposure in real environments, we also introduced other hazardous substances such as silver ions (Ag + ) to the system and then investigated their synergistic nanotoxicity. Our results showed that the exposure to MSiNPs-Ag + and even Ag + at a safe dose, resulted in more significant toxicity than the MSiNPs alone, as evidenced from cell viability, apoptosis, reactive oxygen species (ROS) production, and DNA damage experiments. RNA-Sequencing analysis revealed that the mRNA surveillance signalling pathway plays a unique role in regulating MSiNPs-Ag + -induced cytotoxicity. Besides this, severe corneal damage and dry eye were observed in rat models upon exposure to MSiNPs-Ag + compared to MSiNPs. Most importantly, we also proposed a protein corona-based therapy to treat MSiNP-induced corneal disease, where the corneal damage could be rescued by fetal bovine serum (FBS) treatment.